Parapatric Genetic Lineages Persist in a Multiply Introduced Non-native Bush-Cricket - Kaňuch, Peter; Cassel-Lundhagen, Anna; Preuss, Sonja; Nordlander, Göran; Berggren, Åsa (Frontiers in Ecology and Evolution, 2022)
To understand colonization success of an invasive species we need to know the origin of the founders, where and when they were introduced, and how they spread from the introduction site(s) through the landscape. Admixture of different genetic lineages from multiple introductions is generally hypothesized to be beneficial to invasive species thanks to adaptive variation and heterozygosity-fitness correlations. In this study, population genetic and landscape data was gathered for Roesel’s bush-cricket, Roeseliana roeselii a small bush-cricket common in central and eastern Europe that currently is expanding its range in northern Europe. We examined how colonization history and landscape structure affect the spread of the species and its population genetic structure, as a consequence of multiple introductions. Using comprehensive information of the species ecology and dispersal, together with genetic structure inferred from samples from 29 locations in central Sweden (we employed data published by Preuss et al. 2015), we found that two parapatric founding lineages coexist with very little gene flow during a long time span. An isolation-by-distance pattern and a decrease of genetic diversity towards marginal areas were more pronounced in the lineage situated in forest dominated landscapes. Our findings are in strong contrast to the hypothesis that different genetic lineages will admix when introduced to the same area. The presence of the separate lineages decades after introduction and without physical barriers for gene flow shows that some mechanism prevents them from admixture. One possibility is that the lineages with different genetic setups have adapted independently to local conditions and their admixture resulted in loss of locally adapted genotypes and hybrid offspring, less viable than the respective ancestral genotypes. However, an alternative post-mating reproductive barrier and hybrid breakdown phenomenon should also be considered. Our data indicate that besides landscape characteristics, human transportation of agricultural goods may play an important role for the overall spatial genetic pattern of the species in the study area by aiding the spread of the species.